SAT0505 LONG-TERM FOLLOW-UP IN KAWASAKI SYNDROME: EVIDENCE FROM RETROSPECTIVE MONOCENTRIC DATA IN REAL LIFE. (June 2019) - Maccora, Ilaria; Calabri, Giovanni Battista; Brambilla, Alice; Giani, Teresa; Favilli, Silvia; Cimaz, Rolando; Simonini, Gabriele
Abstract : Background: Kawasaki syndrome (KS) is a severe medium size vasculitis with predilection for coronary arteries, mainly affecting young children. The identification of risk factors for coronary artery lesions (CAL) is the aim of the scientific society in order to early detect patients who need a more aggressive therapy. Objectives: To report clinical data of a monocentric cohort of children with KS over a long-term follow-up. Methods: A monocentric retrospective study between Feb 1982 and Aug 2018, involving children with KS diagnosis followed at the Rheumatology and Cardiology Unit of A. Meyer Children's Hospital. According to cardiac involvement, patients (pts) have been stratified in subject with absence of CAL (no-CAL) and presence of CAL. This latter has been divided in coronary ectasia (CE) and presence of coronary aneurism (CAn). Data analysis was conducted performing a descriptive analysis and assessing risk factors for CAL with analysis of variance (Tukey, LSD and Bonferroni test) and correlation test (Spearman rho test, Chi-square test). Each pt, regardless coronary involvement, underwent a scheduled cardiologic follow-up after 6-8 weeks (6 months, 1 year and ergometric test at 8 years old). Pts with CAL received additionally cardiac evaluations on clinical need. Pts with a follow-up of less than 1 year were excluded from follow-up analyses. Results: Data from 361 pts (219 M, 142 F, aged 1 month-24 years and 5 months) have been reported. Median age of disease onset was 2 years and 1 month; 90% of pts developed the disease < 5 yrs. Disease onset at < 6 months was in 32 patients (8.9%), at < 1 year in 94 (26%). Full clinical data were available in 267 pts. Beside fever, polymorphic rash was in 244 pts (91.4%), conjunctivitis in 229 (85.8%), mucositis in 224 (83.9%), extremities abnormalities in 196 (73.4%) and lymphadenopathies in 165 (61.8%). The average duration of fever was 7 days (range 1-25 days). CAL were detected in 73 pts (20.2%): 58 (16%) had CE, 15 (4.15%) had CAn. Median long-term follow-up was 10 years and 2 months (range 1years – 36 years). The variance analysis in the different groups of CAL showed a significative difference as regard age at disease onset (F= 2.77, p= 0.025), duration of fever (F=16.32, p<0.0001), CRP value (F=6.94, p=0.001) and day of first administration of IVIG (F=7.963 p<0.0001) (Table). A significant correlation between CAL and disease onset at <6 months (ρ=0.137, p=0.009), the need to administer 2 IVIG doses (ρ=0.305, p< 0.001), and male (ρ=-0.109, p=0.038) has been highlighted. At the last follow-up, in the group of no-CAL (261 pts), cardiological visit, ECG, echocardiography and ergometric test (performed 177/261 pts) were normal in all pts. At the last available follow-up, 53 pts with CE had normal cardiological visit, ECG, echocardiography and ergometric test (performed 39/53 pts). Conversely, all 13 pts with CAn showed a normal cardiological visit, whilst ECG was abnormal in 1 patient (7.69%) and echocardiography showed persistent CAn in 8 (61.53%). Ergometric test was performed in 9/13 pts showing abnormal results in one pt (11.11%). Conclusion: Our long-term follow-up in a large, even monocentric, cohort reports possible risk factor of CAL according to current literature. Our long-term follow-up assesses, in real life, the benign course of KS in children without CAL after 6-8 weeks from onset. According to recent guidelines, stopping cardiologic assessment in no risk pts results economically advantageous, timesaving and able to reduce emotional discomfort in children and their families. Disclosure of Interests: Ilaria Maccora: None declared, Giovanni Battista Calabri: None declared, Alice Brambilla: None declared, Teresa Giani: None declared, Silvia Favilli: None declared, Rolando Cimaz: None declared, Gabriele Simonini Grant/research support from: Abbvie, Speakers bureau: Abbvie